(untitled) (Panacea Journal of Medical Sciences, 2024)
Introduction: Endotracheal intubation is one of the most common procedures, and anesthesiologists play an important role in patient care. During laryngoscopy and intubation, the patient can experience rapid and drastic hemodynamic changes that are potentially fatal. Aim: The purpose of this study is to know the efficacy of ivabradine in attenuating the hemodynamic response to laryngoscopy and endotracheal intubation. Materials and Methods: In this prospective randomised double-blinded study, fifty patients belonging to ASA 1 and 2 were randomised to group A - ivabradine 5mg (first dose on the evening before the day of surgery and the second dose one hour before intubation). Patients in group B received tablet MVT (placebo) (first dose on the evening before the day of surgery and the second dose one hour before intubation). Results: Patients in group A showed attenuation of heart rate during laryngoscopy and intubation till 10minutes after intubation. Patients in group B showed a rise in blood pressure during laryngoscopy and intubation till 10 minutes after intubation. Patients in group A and group B showed no significant difference in hemodynamics when monitored intraoperatively. All patients recovered fully from anaesthesia and had no complications such as severe bradycardia. Conclusion: Ivabradine effectively attenuates the hemodynamic stress response without a fall in blood pressure and without severe bradycardia.